Pictures of Childhoods: The Construction of Contemporary Childhoods Through Children’s Drawings and Conversations - Ackesjö, Helena (Journal of Childhood Studies, 2026)
This article explores how contemporary Swedish childhoods are constructed through analysis of 5,933 children’s drawings and conversations about their living conditions and leisure time. Four constructions are identified: scheduled, isolated, digital, and restricted childhoods. These reflect how structural inequalities, material conditions, and place shape children’s opportunities, participation, and agency. While digital spaces offer new forms of belonging, economic and spatial disparities continue to limit children’s participation and well-being. The study highlights the need for educators and policymakers to recognize children’s diverse realities in an emerging class-based society and to promote more just and equitable conditions for all children.